Impact of Dietary Patterns and Nutritional Status on the Academic Performance of Omani School Students - Laila S. Al-Saadi ,; Amanat Ali ,; Mostafa I. Waly ,; K.M. Al-Zuhaibi, (Journal of Pharmacy and Nutrition Sciences, 2020)
In a cross-sectional study, we determined the dietary patterns and nutritional status of Omani school students (12-15 years), and their association with student’s academic performance. A study questionnaire, including a semi-quantitative food frequency questionnaire, was used to collect data. Results indicated that 36% of Omani school students regularly consumed breakfast, whereas only 21.7% had daily 3 meals. Similarly, 30.5% of students consumed fruits ≥ 2 serving/day, 26.6% consumed vegetables ≥ 3 serving/day, and 49.8% consumed fish ≥ 2 serving/week. Significant differences were observed regarding breakfast consumption among genders, regular intake of daily 3 meals, fruits, fish, avoiding soft drinks, nutritional knowledge, total energy and macronutrient intake. Based on BMI, 12.3 % of students were overweight, and 26.1% were obese. The students did not have enough nutritional knowledge and showed unhealthy dietary patterns indicated by their mediocre Omani Diet Scores. Daily energy and macronutrient intakes in males were significantly higher than females. Only fish intake, avoiding soft drinks, waist to height ratio (WHtR), and nutritional knowledge score showed significant associations with student’s academic performance. Healthy dietary patterns and improved nutritional status of school students showed a positive association with their academic performance, suggesting that more focus should be placed in developing healthy dietary patterns.